Just how good is unemployment as a measure of welfare? A note - De Dios, Emmanuel S.; Dinglasan, Katrina (2015)
Governments are rightly concerned with employment generation to make growth inclusive. The use of the open unemployment rate to measure success, however, may be misplaced. In a developing country like the Philippines, with a large informal sector and in the absence of unemployment insurance, open unemployment is primarily a middle-class phenomenon: the unemployed are not predominantly poor, and the poor are not predominantly unemployed. Measures of productivity and shifts of labor across sectors may contain more information and be more welfare-relevant.
Keywords: Unemployment; Underemployment; Labor force